Novel Cardioplegia Delivery in Patients with Severe Aortic Regurgitation - Wang, Chuan; Ma, Weiguo; Gu, Chengxiong; Li, Jingxing (The Thoracic and Cardiovascular Surgeon, 2020)
During aortic valve replacement (AVR) in patients with severe aortic regurgitation (AR), repeated delivery of cardioplegia into the coronary ostia using a routine infusion cannula may induce coronary ostial injury. This study aims to introduce a new no-touch delivery method with reduced time and similar or better outcomes. Preliminary results have shown that no-touch cardioplegia delivery method was a simple, safe, and effective approach for cardioplegia infusion during AVR in patients with severe AR.
Keywords: aortic regurgitation; no-touch cardioplegia delivery method; aortic valve replacement